The gallery of miracles and madness : insanity, modernism, and Hitler's war on art - English, Charlie, 1967* (New York : Random House, 2021)
"This is a tragedy that begins in the halls of psychiatry and modern art and ends in the Nazis' first gas chambers. In the early 1920s, Hans Prinzhorn, a psychiatrist and aesthete, sought insight from the art of mental patients such as Franz Buhler. Buhler was a brilliant, well-known ironworker until his schizophrenia diagnosis, and his work was compared to that of Munch and Duhrer. Prinzhorn collected and published their work, inspiring the Modernist movement that was coming into fashion just as a young Adolf Hitler arrived in Vienna to begin his brief, failed career as a painter. Hitler was alienated by the Modernists and what he called their "degenerate" art that expressed the most primal human emotions. He saw it as a disease in the body politic and set out to crush it with the infamous "Degenerate Art" exhibition Goebbels and Hitler engineered in 1938, that mocked the work of mental patients and Modernists.^
The cultural cleansing was a precursor to the racial cleansing and Prinzhorns's patient artists would be caught up in both. Hitler developed the first gas chambers as a way to dispose of 70,273 patients, including Franz Buhler. In The Gallery of Miracles and Madness, the Nazis' cultural destruction, which would rightly be considered among the lesser sins of the Reich, puts the horror of the Holocaust into relief. The cultural decimation--the burning of books and artwork--was a stepping stone to the more overt horrors of the Holocaust. By equating artistic expression with sickness, Hitler made the case to the German people that they could not be made whole until those spreading this sickness were destroyed.^
Showing us the way Hitler's most profound personal insecurities fan the flames of nationalism and unfolding the transition from Weimar life to Nazi life from less familiar points of view--the ward of a psychiatric hospital, the contents of a museum--English poses profound questions about what is really at stake in cultural objects and offers us a fresh look at the brutality of the Nazi regime"--
The man who jumped in the canal -- A revolutionary for eternal things -- A meeting at Emmendingen -- Dangerous to look at! -- Our sick and troubled times -- Adventures in no-man's land -- Pleasant little pictures -- Dinner with the Bruckmanns -- Glimpses of a transcendental world -- Kunst und Rasse -- The limits of reason -- Cleansing the temple of art -- To be German means to be clear -- The triumph of sterelation -- It cannot be destroyed enough -- Useless eaters -- A bus ride to Grafeneck -- Der Untermensch -- In the madhouse.
Includes bibliographical references (pages [275]-288) and index.
Keywords: National socialism and art; Art and mental illness -- History -- 20th century -- Germany; Prinzhorn, Hans, -- 1886-1933 -- Art collections; Prinzhorn, Hans, -- 1886-1933.; Art -- Destruction and pillage -- History -- 20th century -- Germany; Killing of the mentally ill -- History -- 20th century -- Germany